2012
DOI: 10.1016/j.cell.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protein Synthesis by Ribosomes with a Drug-Obstructed Exit Tunnel

Abstract: The polypeptide exit tunnel is an important functional compartment of the ribosome where the newly synthesized proteins are surveyed. The tunnel is the target of clinically important macrolide antibiotics. Macrolides plug the tunnel and are believed to stop production of all proteins. Contrary to this view, we show that drug-bound ribosomes can synthesize a distinct subset of cellular polypeptides. The structure of a protein defines its ability to thread through the antibiotic-obstructed tunnel. Synthesis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 72 publications
7
160
0
3
Order By: Relevance
“…Our finding that CHL and LZD act at the defined locations within the gene extends the concept of context-specific action of ribosome-targeting inhibitors (32). Macrolides, which bind to the nascent peptide exit tunnel, arrest translation at a limited number of codons within the ORF also depending on the nature of the nascent peptide and of the incoming amino acid (27,28,32,38).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Our finding that CHL and LZD act at the defined locations within the gene extends the concept of context-specific action of ribosome-targeting inhibitors (32). Macrolides, which bind to the nascent peptide exit tunnel, arrest translation at a limited number of codons within the ORF also depending on the nature of the nascent peptide and of the incoming amino acid (27,28,32,38).…”
Section: Discussionmentioning
confidence: 52%
“…As a result, PTC inhibitors halt translation at multiple locations along the gene, whereas macrolides arrest ribosome only at a limited number of codons within the ORF, and synthesis of the proteins lacking the "problematic" sequences may not be inhibited at all (32,39). For this reason, cells treated with excess of macrolide antibiotics continue to synthesize a limited subset of polypeptides (32), whereas protein translation in cells exposed to CHL or LZD is essentially abolished (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, modeling studies have shown that even with a bound macrolide, the tunnel can still accommodate a nascent peptide chain. The macrolide nevertheless greatly hinders the progression of the peptide, which is usually dissociated by the peptidyl‐tRNA drop‐off mechanism before reaching its full size 51, 52. Macrolides have also been shown to block the formation of the large 50S ribosomal subunit by binding to its precursors 53…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%